Clip-reinforced wrapping using the Y-shaped temporalis fascia technique for intracranial aneurysms - Hu, Sheng-Qi; Chen, Ru-Dong; Xu, Wei-Dong; Yu, Jia-Sheng (Frontiers in Surgery, 2022)
Objectives: To identify the effectiveness of the clip-reinforced wrapping using the Y-shaped temporalis fascia (CRYST) technique for treating intracranial aneurysms (IAs). Methods: We retrospectively reviewed five patients with ruptured IAs treated using the CRYST technique from July 2016 to May 2021. Three patients had blood blister-like aneurysms (BBAs) (one with intraoperative rupture), and two had anterior communicating artery (AcoA) aneurysms (one with intraoperative rupture). All patients had intraoperative indocyanine green angiography, and digital subtraction angiography (DSA) was reviewed 10–14 days after surgery. At one year postoperatively, three patients (two BBAs and one AcoA aneurysm) underwent DSA, and two patients (one BBA and one AcoA aneurysm) underwent computed tomographic angiography (CTA). Results: Two aneurysms ruptured intraoperatively during the clipping, and no severe complications occurred. No patients had neurological deficits after surgery and they had good outcomes. Four DSAs showed no aneurysms and no significant stenosis of the parent artery 10–14 days after surgery. One patient had mild stenosis of the parent artery on DSA ten days after surgery; the stenosis improved on DSA one year after surgery. No other aneurysms recurred, and parent arteries were clear on CTA or DSA one year after surgery. Conclusions: Combining our accumulated experience in the work and literature, we described the CRYST technique to treat intractable IAs with specific morphologies and irregular wall structures in our patients. All outcome and follow-up results were favorable.